Benefits of Complementary Integrative Practices (PICs) in labor (Research, Society and Development, 2022)
Objective: To understand how PICS are used during labor. Methodology: this is an integrative review based on the literature on the subject under study. Based on scientific articles located in the Scielos and BVS databases in scientific works from 2015 to 2021, using the following descriptors: Humanized childbirth, PICS in labor. Conclusion: it was generally demonstrated that PICS contribute positively to labor, as they are capable of inducing labor, relieving pain and favoring the progression of parturition. The use of PICS is able to reduce the time of delivery, assist in fetal positioning and also in the physical and mental reestablishment of the puerperal woman. It is suggested that PICS be widely disseminated and worked on in universities, expanding the training of professionals.